Bioconversion of ω-fatty acid from giant snakehead (Channa micropeltes) fish oil - Omar, Muhammad Nor; Yusoff, Nur Shahidatul Ahlam Md; Yunus, Kamaruzzaman (2009)
Study on bioconversion of ω-fatty acid contained in Channa micropeltes fish oil was carried out using guinea pig lung homogenate. The fish oil of C. micropeltes was incubated aerobically at 37oC in phosphate buffer solution with the addition of guinea pig lung homogenate. After incubation it was found that ca. 76% arachidonic acid has been converted to the prostaglandin metabolite. The fatty acid constituents in fish oil were analysed by GC-MS after the acids have been methylated.